2019
DOI: 10.3390/w11050923
|View full text |Cite
|
Sign up to set email alerts
|

Growth and Nutrient Removal Efficiency of Sweet Wormwood (Artemisia annua) in a Recirculating Aquaculture System for Nile Tilapia (Oreochromis niloticus)

Abstract: The maintenance of optimal water quality for fish production is one of the major challenges in aquaculture. Aquaponic systems can improve the quality of water for fish by removing the undesirable wastes and in turn produce a second marketable crop. However, there is no information on the growth and nutrient removal capability of Artemisia annua in aquaponic systems. This study evaluated the effect of plant density on water quality, the growth of A. annua and Oreochromis niloticus in a small scale aquaponic sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 41 publications
1
12
0
1
Order By: Relevance
“…The trend in ammonia and nitrate levels suggest that microbial activity that oxidizes ammonia and converts nitrates to nitrogen gas favoured the removal of nutrients from the hydroponic subsystem. Similar media-based aquaponic studies demonstrated that microbial organisms play a significant role in removing nutrients from aquaculture wastewater (Gichana et al 2019;Boxman et al 2017;Hu et al 2015;Trang and Brix 2014). Gichana et al (2019) demonstrated that plant uptake did not contribute significantly to the overall removal of nutrients in a media-based system because a hydroponic subsystem without plants played a role in the removal of nutrients from the effluent water.…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations
“…The trend in ammonia and nitrate levels suggest that microbial activity that oxidizes ammonia and converts nitrates to nitrogen gas favoured the removal of nutrients from the hydroponic subsystem. Similar media-based aquaponic studies demonstrated that microbial organisms play a significant role in removing nutrients from aquaculture wastewater (Gichana et al 2019;Boxman et al 2017;Hu et al 2015;Trang and Brix 2014). Gichana et al (2019) demonstrated that plant uptake did not contribute significantly to the overall removal of nutrients in a media-based system because a hydroponic subsystem without plants played a role in the removal of nutrients from the effluent water.…”
Section: Discussionmentioning
confidence: 92%
“…Similar media-based aquaponic studies demonstrated that microbial organisms play a significant role in removing nutrients from aquaculture wastewater (Gichana et al 2019;Boxman et al 2017;Hu et al 2015;Trang and Brix 2014). Gichana et al (2019) demonstrated that plant uptake did not contribute significantly to the overall removal of nutrients in a media-based system because a hydroponic subsystem without plants played a role in the removal of nutrients from the effluent water. In Trang and Brix (2014), plants absorbed only 6% of nitrogen and 7% of phosphorus while 45% of nitrogen and 9% of phosphorus was unaccounted for suggesting that the unaccounted nitrogen and phosphorus was probably bound in the media substrate or lost through denitrification.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…Introduction of aquatic phytoremediation plant species and adsorbents should be performed in land management plans in order to reduce risks due to their contamination [22]. Therefore, plants represent an alternative remediation approach has escalated in the last few decades, [23][24][25][26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%